The natural gas sector in Bolivia: An overview - Lykke E. Andersen; Mauricio Meza (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2001)
This paper provides a thorough overview of the natural gas sector in Bolivia, with the purpose of identifying critical questions to be answered in subsequent research. The paper shows that the Bolivian benefits from natural gas exports are rather limited. The sector generates very little employment, there are few linkages with the rest of the economy, and most of the profits accrue to foreigners. The royalties and tax income that remain in Bolivia are highly volatile and may amount to anything between US 85 million and US 1.4 billion per year, depending on the development of international oil prices. The high volatility is cause for concern, since Bolivia's tax system relies heavily on the hydrocarbon sector for revenues. Another cause for concern is the uneven distribution of benefits across departments. Tarija, which holds 80% of certified natural gas resources but only 5% of the Bolivian population, will receive substantial additional resources through royalties. This windfall may cause localized problems in terms of rent seeking behavior and corruption, displacement of other productive sectors, under-development of alternative tax-bases, and addiction to easy natural gas dollars.
Keywords: 330; Gaswirtschaft; Bolivien